Preliminary Evidence of Reduced Urge to Cough and Cough Response in Four Individuals following Remote Traumatic Brain Injury with Tracheostomy. (27th September 2016) - Silverman, Erin; Sapienza, Christine M.; Miller, Sarah; Carnaby, Giselle; Levy, Charles; Tsai, Hsiu-Wen; Davenport, Paul W.
Abstract : Cough and swallow protect the lungs and are frequently impaired following traumatic brain injury (TBI). This project examined cough response to inhaled capsaicin solution challenge in a cohort of four young adults with a history of TBI within the preceding five years. All participants had a history of tracheostomy with subsequent decannulation and dysphagia after their injuries (resolved for all but one participant). Urge to cough (UTC) and cough response were measured and compared to an existing database of normative cough response data obtained from 32 healthy controls (HCs). Participants displayed decreased UTC and cough responses compared to HCs. It is unknown if these preliminary results manifest as a consequence of disrupted sensory (afferent) projections, an inability to perceive or discriminate cough stimuli, disrupted motor (efferent) response, peripheral weakness, or any combination of these factors. Future work should attempt to clarify if the observed phenomena are borne out in a larger sample of individuals with TBI, determine the relative contributions of central versus peripheral nervous system structures to cough sensory perceptual changes following TBI (should they exist), and formulate recommendations for systematic screening and assessment of cough sensory perception in order to facilitate rehabilitative efforts. This project is identified with the National Clinical Trials NCT02240329 .